1992
DOI: 10.1161/01.str.23.8.1118
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived nitric oxide synthase inhibition. Effects on cerebral blood flow, pial artery diameter, and vascular morphology in rats.

Abstract: Background and Purpose:We determined the effects of inhibiting the production of cerebral endothelium-derived nitric oxide on pial artery diameter, cortical blood flow, and vascular morphology.Methods: An inhibitor of endothelium-derived nitric oxide synthesis, JV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(43 citation statements)
references
References 33 publications
0
42
1
Order By: Relevance
“…However, it may be noted that under pentobarbitone anaesthesia, capillary blood flow is approximately one-third of the total carotid blood flow (Saxena & Verdouw, 1982;1985;Den Boer et al, 1992;present results) and thus the basal release of NO may already be too low to detect a significant decrease. In contrast to a number of studies which reported a moderate reduction in cerebral blood flow following NOsynthase inhibition, suggesting a basal NO-release in this part of the cranial circulation (Kovaich et al, 1992;Prado et al, 1992;Seligsohn & Bill, 1993), in our present experiments L-NAME failed to reduce the cerebral component of carotid blood flow. The absence of an endothelial NO-dependent dilator tone is supported by the recent finding that cultured rat brain microvessel endothelial cells do not show basal release of NO (Durieu-Trautmann et al, 1993).…”
Section: Regional Carotid Bloodflowcontrasting
confidence: 99%
“…However, it may be noted that under pentobarbitone anaesthesia, capillary blood flow is approximately one-third of the total carotid blood flow (Saxena & Verdouw, 1982;1985;Den Boer et al, 1992;present results) and thus the basal release of NO may already be too low to detect a significant decrease. In contrast to a number of studies which reported a moderate reduction in cerebral blood flow following NOsynthase inhibition, suggesting a basal NO-release in this part of the cranial circulation (Kovaich et al, 1992;Prado et al, 1992;Seligsohn & Bill, 1993), in our present experiments L-NAME failed to reduce the cerebral component of carotid blood flow. The absence of an endothelial NO-dependent dilator tone is supported by the recent finding that cultured rat brain microvessel endothelial cells do not show basal release of NO (Durieu-Trautmann et al, 1993).…”
Section: Regional Carotid Bloodflowcontrasting
confidence: 99%
“…Finally, it has been shown that NO can increase cerebral blood flow (Prado et al, 1992) by releasing vascular smooth muscle cells (Moncada et al, 1991). Therefore, the microiontophoretic application of SNOG or L-NAME could influence the microvascular tone by interfering with NO formation.…”
Section: Possible Mechanisms Involved In the No-dependent Modulation mentioning
confidence: 99%
“…In deeper cerebral tissue, however, such a contribution may be of functional importance (Tanaka et al, 1991;Pellegrino et al, 1992). Others find this to be valid also in cortical vessels (Faraci, 1991; Tanaka et al, 1991;Prado et al, 1992). Such discrepancies may at least partly result from meth odological differences.…”
mentioning
confidence: 95%